Eksposisi Eksegetis Konsep "Manusia Baru" 2 Korintus 5:17 dalam Teologi Dispensasional - Yeffry Hendra Lesmana; Lexie Adrin Kembuan (Angelion, 2026)
This study aims to analyze the concept of the new creation in 2 Corinthians 5:17 from the perspective of Dispensational Theology. The study is motivated by the observation that previous research has predominantly employed historical, linguistic, systematic theological, and Reformed approaches, while giving insufficient attention to the progressive unfolding of God's revelation throughout redemptive history. This research employs a qualitative method using a library research approach. The primary data consist of the biblical text of 2 Corinthians 5:17 in the original Greek language along with several Bible translations, whereas the secondary data are drawn from biblical theology, systematic theology, dispensational theology, biblical dictionaries, and relevant scholarly publications. Data were analyzed through a grammatical-historical exegetical approach, including lexical, grammatical, syntactical, and contextual analyses, which were subsequently synthesized within the framework of dispensational hermeneutics. The findings reveal that the term kain? ktisis (“new creation”) refers to God's supernatural creative work through regeneration by the Holy Spirit, whereby believers receive a new ontological identity in Christ. This concept signifies not merely a moral transformation but a comprehensive renewal resulting from Christ's redemptive work. From a dispensational perspective, the new creation represents the positional reality of believers in the Dispensation of Grace and forms part of the progressive development of God's redemptive plan without eliminating the distinction between God's program for the Church and His program for Israel. Therefore, this study contributes to theological scholarship by providing a more comprehensive understanding of the concept of the new creation through interpreting 2 Corinthians 5:17 within the broader framework of God's redemptive history.   Penelitian ini bertujuan untuk menganalisis konsep manusia baru dalam 2 Korintus 5:17 berdasarkan perspektif Teologi Dispensasional. Kajian ini dilatarbelakangi oleh kecenderungan penelitian sebelumnya yang lebih banyak menggunakan pendekatan historis, linguistik, teologi sistematika, dan reformatoris, sehingga belum memberikan perhatian yang memadai terhadap perkembangan progresif penyataan Allah dalam sejarah penebusan. Penelitian menggunakan metode kualitatif dengan pendekatan studi kepustakaan (library research). Data primer berupa teks Alkitab, khususnya 2 Korintus 5:17 dalam bahasa Yunani beserta berbagai terjemahannya, sedangkan data sekunder diperoleh dari literatur teologi biblika, teologi sistematika, teologi dispensasional, kamus biblika, dan artikel ilmiah yang relevan. Analisis dilakukan melalui pendekatan eksegesis gramatikal-historis yang meliputi studi leksikal, gramatikal, sintaksis, dan analisis konteks, kemudian disintesiskan dalam kerangka hermeneutika dispensasional. Hasil penelitian menunjukkan bahwa istilah kain? ktisis (ciptaan baru) menunjuk pada karya kreatif Allah yang bersifat supranatural melalui kelahiran baru oleh Roh Kudus, sehingga orang percaya menerima identitas ontologis yang baru di dalam Kristus. Konsep ini tidak sekadar menggambarkan perubahan moral, tetapi menegaskan transformasi menyeluruh sebagai hasil karya penebusan Kristus. Perspektif Teologi Dispensasional memperlihatkan bahwa ciptaan baru merupakan realitas posisi orang percaya dalam Dispensasi Kasih Karunia, sekaligus bagian dari perkembangan progresif rencana keselamatan Allah tanpa menghapus pembedaan antara program Allah bagi Gereja dan Israel. Dengan demikian, penelitian ini memberikan kontribusi teologis dalam memperkaya pemahaman mengenai manusia baru dengan menempatkan 2 Korintus 5:17 dalam keseluruhan sejarah penebusan Allah secara komprehensif.